COMORBIDITY OF NON-ALCOHOLIC FATTY LIVER DISEASE AND PSORIASIS - Трухан, Дмитрий Иванович; Филимонов, Сергей Николаевич (Medicine in Kuzbass, 2025)
Non-alcoholic fatty liver disease (NAFLD) is currently the most common chronic non-infectious liver disease and affects 25 to 30% of adults in most countries. Psoriasis is one of the most common skin diseases and occurs in 2-3% of the population of countries, it affects about 125 million people worldwide Previously, psoriasis was considered exclusively as a skin disease, but from the standpoint of today, psoriasis is considered as a chronic multifactorial, multisystem, immune-mediated inflammatory disease with a complex pathogenetic mechanism caused by chronic activation of adaptive and innate immune responses due to excessive proliferation of keratinocytes with the development of latent multi-organ cellular destruction and dysfunction. We searched the Pubmed and Scopus information databases for sources published before 01/30/2025, which considered the direct relationship between NAFLD and psoriasis. The results of epidemiological and clinical studies, their generalization in systematic reviews and meta-analyses, indicate the presence of a bidirectional relationship between NAFLD and psoriasis. The mechanisms of the relationship include similar risk factors, close pathophysiological processes, including comparable immunopathogenic mechanisms (primarily the participation of IL-17, IL-6, TNF-α and Th17) and common inflammatory pathways. When treating comorbid patients with NAFLD and psoriasis, interaction and close cooperation between a gastroenterologist/hepatologist and a dermatologist are advisable. Ursodeoxycholic acid can be considered as a component of therapy in comorbid patients with NAFLD and psoriasis, affecting both diseases.